2013
DOI: 10.19026/ajas.5.4841
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bee Pollinators in Improving Berry Weight and Coffee Cup Quality

Abstract: The study was conducted at Kiambu County in Kenya. The aim of this study was to investigate whether pollination improves the coffee yield and quality of processed coffee in terms of taste and aroma. Among the parameters evaluated when grading coffee for sale in world market are berry weight and cup quality. No previous work in Kenya describes the role of bee pollinators in enhancement of coffee yields and quality. Data on berry weights and the resulting processed coffee quality from different pollination level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
2
Order By: Relevance
“…The coffee beans produced by closed pollination were slightly shorter than other groups (ANOVA, P<0,05), while other parameters were relatively similar among all groups (Table 1). A study by Karanja et al [16] showed that coffee bean weight and coffee cup quality were affected by pollination types (in open and hand pollination), which means pollination not only increases crop yields but also improves the taste and coffee aroma. This study also supported the importance of non-managed social bees as pollinators of coffee, as shown by bigger fruit produced through open pollination [17].…”
Section: Resultsmentioning
confidence: 99%
“…The coffee beans produced by closed pollination were slightly shorter than other groups (ANOVA, P<0,05), while other parameters were relatively similar among all groups (Table 1). A study by Karanja et al [16] showed that coffee bean weight and coffee cup quality were affected by pollination types (in open and hand pollination), which means pollination not only increases crop yields but also improves the taste and coffee aroma. This study also supported the importance of non-managed social bees as pollinators of coffee, as shown by bigger fruit produced through open pollination [17].…”
Section: Resultsmentioning
confidence: 99%
“…Pengelompokan mutu fisik biji kopi juga berdasarkan ukuran dan cacat biji (Muzaifa et al, 2016). Biji kopi berukuran lebih besar cenderung mendapatkan harga yang relatif lebih tinggi (Karanja et al, 2013). Biji kopi yang berukuran besar dan seragam akan menghasilkan keseragaman kualitas pada hasil pemanggangan (roasting) dan tidak cepat gosong (Nathsubedi, 2011).…”
Section: Ukuran Bijiunclassified
“…Biji kopi berukuran lebih besar cenderung mendapatkan harga yang relatif lebih tinggi (Priyono & Sumirat, 2012;Karanja, Njoroge, Kihoro, Gikungu, & Newton, 2013). Biji kopi yang berukuran besar dan seragam akan menghasilkan keseragaman kualitas pada hasil pemanggangan (roasting) dan tidak cepat gosong (Nathsubedi, 2011).…”
Section: Pendahuluanunclassified